Lichen ruber planus as a psychiatric problem - Gruden-Pokupec, Josipa-Sanja; Gruden, Vladimir, st.; Gruden, Vladimir, ml. (2009)
Our mouth is the mirror of our health and it might be said that numerous diseases which affect our organism may be manifested in the mouth. Early symptoms occurring within the oral cavity may emerge with diseases related to our blood system, gastrointestinal system, renal system, cardiovascular system, and mental system. The most frequent psychogenic diseases which may lead to the emerging of lichen planus are depression, anxiety and stress. Depression is a condition of decreased psychophysical activity predominated by sadness, apathy and slowed-down pessimistic thinking. Anxiety is a complex feeling comprising anxiety, fear, tension and insecurity, and is accompanied by the activation of autonomic nervous system. Stress is a reaction to trauma, and it enhances survival.
Bibliografija: 9 jed
Keywords: Lichen ruber planus -- Depresija -- Anksioznost -- Stres